A subnational socioeconomic assessment of family planning levels, projections, and disparities among married women of reproductive age in Cameroon - Raïssa Shiyghan Nsashiyi; Md Mizanur Rahman; Lawrence Monah Ndam; Masahiro Hashizume (PLoS ONE, 2025)
Background Local-level socioeconomic gradients significantly influence access to reproductive health services in developing countries. This study examines disparities in family planning use among married women of reproductive age across Cameroon’s subnational territories, highlighting inequities often overlooked in national analyses. Furthermore, it incorporates HIV status (a key yet frequently omitted covariate) into the assessment of family planning determinants. Methods A Bayesian hierarchical model incorporated with Cameroon Demographic and Health Survey cross-sectional data (between 1991 and 2018) was employed to generate estimates of family planning indicators per residence, wealth, and education categories within each region. Slope index of inequality was used to quantify disparities. The determinants analysis involved Bayesian logistic regression. Results Estimates for 2023 revealed that the Centre region’s urban and rural areas had the highest modern contraceptive prevalence rate overall, with 49.0% (24.9–73.8) and 28.2% (12.4–52.3), respectively. The rural Far North had the least estimate [3.9% (1.5–10.5)]. Demand satisfied with modern methods was highest among Adamawa region’s richest quintile [82.9% (58.1 to 94.4)] and higher educated [85.9% (69.5 to 94.2)], and lowest among the East region’s poorest [5.3% (1.5 to 16.5)] and Far North’s none-educated [8.6% (3.3 to 20.4)]. Unmet need for modern methods was lowest among the West region’s richest [5.1% (1.8 to 13.5)] and highest among the Littoral’s poorest [23.1% (9.4 to 47.4)]. 2030 projections show the widest wealth- and education-based gaps for demand satisfied with modern methods in the Adamawa [27.0 percentage points (%p) (2.3 to 51.6) and 79.3%p (73.9 to 84.7), respectively]. Age ≥  20 years, higher education level, practising Catholic/Christian religion, having ≥  one living child(ren), and higher household wealth quintile, were associated with increased odds of modern contraceptive use. Conclusion Increased focus is essential on rural, poorer, and less educated populations, particularly in the Northern regions, to effectively address family planning inequities across Cameroon.